Creation and validation of a health guidance booklet for family members of children with sickle cell disease - Sarah Vieira Figueiredo; Thereza Maria Magalhães Moreira; Clarice Santos Mota; Roselene Soares de Oliveira; Ilvana Lima Verde Gomes (Universidade Federal do Rio de Janeiro, 2019)
ABSTRACT The aim of this study was to elaborate a booklet for health follow-up and guidance on sickle cell disease for relatives of children with this disease and validate it. It is a methodological study, conducted from May 2017 to February 2018, of the elaboration and validation of an educational technology, constructed from previous field research in a pediatric hospital in Ceará (ethical opinion nº 994.879 and nº 955.727). Validation of content and appearance occurred by specialized, technical and communication judges; after the adjustments, the evaluation by representatives of the target public took place. The analysis was through the Concordance Index. Results: the evaluation of technical judges and experts reached a Global Concordance Index of 0.93, characterizing the book as good quality. The judges of communication evaluated all items as Superior. As for family members, everyone agreed that the book was adequate. It is concluded that the booklet has been duly drawn up and validated as regards its content and its appearance. Implications for practice: this educational technology is an important instrument to be used by health professionals, aiming to contribute to increase the knowledge of the relatives of children with sickle cell disease.